2020
DOI: 10.1371/journal.pone.0225820
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-155 governs SHIP-1 expression and localization in NK cells and regulates subsequent infiltration into murine AT3 mammary carcinoma

Abstract: NK cell migration and activation are crucial elements of tumor immune surveillance. In mammary carcinomas, the number and function of NK cells is diminished, despite being positively associated with clinical outcome. MicroRNA-155 (miR-155) has been shown to be an important regulator of NK cell activation through its interaction with SHIP-1 downstream of inhibitory NK receptor signaling, but has not been explored in regard to NK cell migration. Here, we explored the migratory potential and function of NK cells … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 43 publications
0
17
0
Order By: Relevance
“…In the searching for the most prominent targets of miR-155 in odontoblast, our bioinformatics results con rmed that SHIP1 was one of the most important factors in dental in ammation. Many reports have stated that SHIP1 is a key factor for miR-155 regulation in in ammation, brosis, and other immune processes [14,21,35]. We veri ed that miR-155 directly interacted and regulated the expression of SHIP1 in pulpal in ammation.…”
Section: Discussionmentioning
confidence: 65%
“…In the searching for the most prominent targets of miR-155 in odontoblast, our bioinformatics results con rmed that SHIP1 was one of the most important factors in dental in ammation. Many reports have stated that SHIP1 is a key factor for miR-155 regulation in in ammation, brosis, and other immune processes [14,21,35]. We veri ed that miR-155 directly interacted and regulated the expression of SHIP1 in pulpal in ammation.…”
Section: Discussionmentioning
confidence: 65%
“…Recent studies have identi ed miR-155 as critical regulators in various physiological and pathologic processes, including hematopoietic stem-progenitor cells differentiation, in ammation, infections, and immune process of cancer formation [19,20,21]. The different functions of miR-155 in different tissues, is calling for studies to identify its role in particular circumstances.…”
Section: Discussionmentioning
confidence: 99%
“…It is suggested that miR-155 may promote chemotaxis by regulating the receptors of CCL2 on NK cells. 204 In mesenchymal stem cells, Sirt1, the closest mammalian homolog of yeast Sir2, promoted the expression of CXCL10, which then recruited NK cells to effectively inhibit tumor growth. 205 CXCL12, a chemokine secreted by hepatic stellate cells, induced NK cell quiescence through its receptor, CXCR4, promoting breast cancer outgrowth.…”
Section: Trafficking Of Nk Cells Into Tumorsmentioning
confidence: 99%